The effect of adjustment announcement of predicted profit on price and trading volume of listed companies in Tehran Stock Exchange - Majid Pakdel; Abbbas Talebbeydokhti (Dutch Journal of Finance and Management, 2018)
This study investigated the effect of adjustment announcement of predicted profit on price and stocks trading volume of listed companies in Tehran Stock Exchange, in order to determine whether the declaration of adjusted earnings forecast have effect on the two parameters of price and trading volume of the stock or not. In other words, do the declaration adjusted earnings forecast have information content? Therefore, after review of literature collection and formulating hypotheses, data of studied companies was collected and prepared by researchers and eventually the hypotheses were used by econometric models and descriptive statistics and using the Ewies software. The results showed that there was a significant relationship between the amount of the dividend announcement and the date of the announcement; also, there was a significant relationship between the announcement date and the amount of profit with a turnover. So, the announcement of adjusted predicted profit has effect on the stock price and trading volume of stocks.
Keywords: 650; adjusted predicted profit; stock price; trading volume of stocks